Sensitivity model based PID controller for various high-order processes. Issue 6 (24th October 2019) - Ghosh, Sreya; Pan, Somnath
Abstract : Purpose: This paper aims to propose a reference model based simple strategy for the design of proportional-integral-derivative (PID) controller using frequency response matching for high-order stable, integrating and unstable processes that may have time-delay and non-minimum phase zero. Design/methodology/approach: The reference sensitivity model is designed fulfilling stability conditions of the control system responses such as set-point response, load-disturbance response and noise response along with transient response criteria. The analytical controller thus designed is approximated to a PID controller using a simple formula based on a model-matching technique at low frequency. Findings: PID controllers are designed for examples with varied dynamics taken from the literature, and the performances of the designed control systems are compared with some methods prevalent in the literature to show the efficacy of the proposed work. Overall, the method gives satisfactory set-point, as well as load-disturbance responses and controller-outputs in all the cases considered. Originality/value: The method is applicable to high-order processes of various monotonic or oscillating dynamics without requiring process reduction. The PID controller designed considering a reference model with suitable criteria ensuring stability and a modified model matching technique, which provides a stable control system for all these high-order processes.